Can we accurately diagnose minute gastric cancers (≤5 mm)? Chromoendoscopy (CE) vs magnifying endoscopy with narrow band imaging (M-NBI) - Fujiwara, Shoko; Yao, Kenshi; Nagahama, Takashi; Uchita, K.; Kanemitsu, Takao; Tsurumi, Kozue; Takatsu, Noritaka; Hisabe, Takashi; Tanabe, Hiroshi; Iwashita, Akinori; Matsui, Toshiyuki (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2015)
Background Chromoendoscopy (CE) is relatively ineffective at identifying the cancer-specific morphological characteristics of minute gastric cancers less than or equal to 5 mm in diameter, and on its own is insufficient to make an accurate diagnosis. The aim of this study is to assess the diagnostic performance of magnifying endoscopy with narrow band imaging (M-NBI) for minute gastric cancers. Methods The minute cancer group comprised consecutive endoscopic submucosal dissection-resected minute gastric cancers histologically measured as no larger than 5 mm in diameter. The non-cancer group comprised consecutive non-cancer lesions no larger than 5 mm in diameter. The two groups were subject to retrospective analysis to evaluate the diagnostic ability (sensitivity, specificity, and diagnostic accuracy) and reproducibility of CE and M-NBI. Results The results for CE versus M-NBI were as follows: sensitivity 43.7 % (95 % CI, 26.5–61.0 %) versus 78.0 % (95 % CI, 64.0–92.0 %); specificity 81.6 % (95 % CI, 72.6–90.6 %) versus 92.9 % (95 % CI, 87.0–98.9 %); and diagnostic accuracy 69.9 % (95 % CI, 61.0–78.6 %) versus 88.3 % (95 % CI, 82.0–94.5 %). The sensitivity and diagnostic accuracy were, therefore, significantly higher for M-NBI than for CE. The inter-observer variability was κ = 0.08 for CE and κ = 0.56 for M-NBI, while the intra-observer variability was κ = 0.38 and κ = 0.65, respectively. Conclusions M-NBI has greater sensitivity and reproducibility than CE for the diagnosis of minute gastric cancers.